Bridging Intravenous Thrombolysis Before Mechanical Thrombectomy for Large Artery Occlusion May be Detrimental with Thrombus Fragmentation - Yi, Ho J.; Sung, Jae Hoon; Lee, Dong Hoon (Current Neurovascular Research, 2020)
Objective: We investigated whether intravenous thrombolysis (IVT) affected the outcomes and complications of mechanical thrombectomy (MT), specifically focusing on thrombus fragmentation. Methods: The patients who underwent MT for large artery occlusion (LAO) were classified into two groups: MT with prior IVT (MT+IVT) group and MT without prior IVT (MT-IVT) group. The clinical outcome, successful recanalization with other radiological outcomes, and complications were compared, between two groups. Subgroup analysis was also performed for patients with simultaneous application of stent retriever and aspiration. Results: There were no significant differences in clinical outcome and successful recanalization rate, between both groups. However, the ratio of pre- to peri-procedural thrombus fragmentation was significantly higher in the MT+IVT group (14.6% and 16.2%, respectively; P=0.004) compared to the MT-IVT group (5.1% and 6.8%, respectively; P=0.008). The MT+IVT group required more second stent retriever (16.2%), more stent passages (median value = 2), and more occurrence of distal emboli (3.9%) than the MT-IVT group (7.9%, median value = 1, and 8.1%, respectively) (P=0.004, 0.008 and 0.018, respectively). In subgroup analysis, the results were similar to those of the entire patients. Conclusion: Thrombus fragmentation of IVT with t-PA before MT resulted in an increased need for additional rescue therapies, and it could induce more distal emboli. The use of IVT prior to MT does not affect the clinical outcome and successful recanalization, compared with MT without prior IVT. Therefore, we need to reconsider the need for IVT before MT.
Keywords: thrombectomy